PENINGKATAN MOTIVASI DAN PRESTASI BELAJAR SISWA MELALUI METODE GROUP INVESTIGATION PEMBELAJARAN PAI DI SMA - Sy. Abdul Hakim (Universitas Tanjungpura, 2022)
This research is motivated by increasing students' motivation and achievement in learning PAI through the Group Investigation Method in class XI of SMK Negeri 4 Pontianak. The results of this study. Based on the results of research and discussion, the following conclusions can be drawn: The use of the Group Investigation method significantly affects the learning motivation of Class XI students to increase, seen from the qualitative average value of Cycle I 1.76, cycle I is 2.72, and in cycle II there are 2.83. The use of the Group Investigation method significantly affects the learning achievement of class XI students to increase, judging from the results of the average competencytest class in Cycle I with an average of 45.52, Cycle I is 79.41, and in Cycle II there is 81.75. The use of a variety of learning methods, namely Group Investigation.